PERKEMBANGAN PONDOK PESANTREN TARBIYAH ISLAMIYAH KOTO TINGGI PANDAI SIKEK KECAMATAN X KOTO KABUPATEN TANAH DATAR TAHUN 1942-2013 - Alwahid, Ibnu Habib (Pendidikan Sejarah, 2014)
This paper examines the process of the establishment of boarding school Tarbiyah Islamiyah High Koto Clever Sikek. Starting on 1 April 1942 there were 4 students who study in boarding school was initially studied in the surau. Limitations of this study is the beginning of the year 1942 was the establishment of boarding school Tarbiyah Islamiyah High Koto Clever Sikek. Limitations of this study is the end of 2013 since this year boarding school Tarbiyah Islamiyah High Clever Sikek Koto looks more and more development and the number of students who go to this boarding school. The collection of data sources (heuristic) is done in two ways. Based on the process that has been done penelitin note that the establishment of Pondok Pesantren Tarbiyah Islamiyah Tuah Clever Sikek on April 1, 1942 the first leader that is H.Ibrahim, both AD Labai Bandaro leaders, leaders Ummy Rosda third, and fourth leader Sabirin Tuanku Mudo. At the time of this leadership Sabirin Tuanku Mudo Pondok Pesantren Tarbiyah Islmiyah Tuah Clever Sikek experiencing very rapid growth, so the number of santri and adequate facilities and infrastructures have started from the previous manager the Pondok Pesantren Tarbiyah Islamiyah Tuah Clever Sikek able to create awareness to the local community, and the public outside the district Clever Sikek to learn / deepen religious knowledge, so that was the end of santris Pesantren is able to compete with other pesantren in many santris prove it has become in Pondok Pesantren Kyai, Poolri members, civil servants and some became professors.